2009
DOI: 10.3892/or_00000436
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in cervical cancer is mediated by HeLa metabolites through endothelial cell tissue kallikrein

Abstract: Abstract. High vascularity correlates with poor clinical outcome in cancer of the uterine cervix. We investigated whether human cervical cancer cell (HeLa) metabolites influenced endothelial cell proliferation through the serine protease, tissue kallikrein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…With the recent discovery of all of the fifteen members of the KLK family, increasing evidence has indicated that KLKs may play pivotal roles in breast cancer progression and metastasis (Table 4, Figure 1,2). 6,6365 In normal breast tissue, all fifteen KLKs have been identified, either at the mRNA and/or the protein level 23,66. KLK15 mRNA is not expressed by normal breast tissue, low to moderate mRNA levels are detected for KLK2–5, 9, 12 and 13 , high ones for KLK1, 6–8, 10, 11 and 14.…”
Section: Klk Expression In Breast Cancermentioning
confidence: 99%
“…With the recent discovery of all of the fifteen members of the KLK family, increasing evidence has indicated that KLKs may play pivotal roles in breast cancer progression and metastasis (Table 4, Figure 1,2). 6,6365 In normal breast tissue, all fifteen KLKs have been identified, either at the mRNA and/or the protein level 23,66. KLK15 mRNA is not expressed by normal breast tissue, low to moderate mRNA levels are detected for KLK2–5, 9, 12 and 13 , high ones for KLK1, 6–8, 10, 11 and 14.…”
Section: Klk Expression In Breast Cancermentioning
confidence: 99%
“…61,62 While communication between cervical cancer cells and endothelial cells has been investigated in vitro, all of these studies have been done with either conditioned media, which does not allow for crosstalk, or transwell assays, which do not enable juxtracrine signaling or observation of 3D behavior. [63][64][65] Therefore, this work is the first to evaluate the role of cervical cancer-endothelial cell crosstalk on cervical cancer invasion or microvessel formation in an in vitro model. The results of our DOE revealed a complex nonlinear relationship between fibrin and collagen concentrations in the bottom hydrogel on both endothelial cell and cervical cancer behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cell proliferation is an integral component of pro-angiogenic response [ 59 ]. HeLa cells are known to release serine protease tissue Kallikrein that induced endothelial cell proliferation [ 60 ]. Incidentally, multiplex proximity extension assays on exosomal proteome showed presence of Kallikrein in human milk and prostate cancer exosomes [ 61 ], which suggests that pro-angiogenic proteins like Kallikrein may be directly exported through exosomes.…”
Section: Discussionmentioning
confidence: 99%